Hepatic Oxygenation Changes and Symptomatic Intradialytic Hypotension - Susumu Ookawara; Kiyonori Ito; Yusuke Sasabuchi; Yuichiro Ueda; Junki Morino; Shohei Kaneko; Yuko Mutsuyoshi; Taisuke Kitano; Keiji Hirai; Yoshiyuki Morishita (Karger Publishers, 2024)
Introduction: Clinical studies on differences among changes in cerebral and hepatic oxygenation during hemodialysis (HD) in patients with and without intradialytic hypotension (IDH) are limited. We investigated changes in intradialytic cerebral and hepatic oxygenation before systolic blood pressure (SBP) reached the nadir during HD and compared these differences between patients with and without symptomatic IDH. Methods: We analyzed data from 109 patients with (n=23) and without (n=86) symptomatic IDH who were treated with HD. Cerebral and hepatic regional oxygen saturation (rSO2), as a marker of tissue oxygenation and circulation, was monitored during HD using an INVOS 5100c oxygen saturation monitor. Changes in cerebral or hepatic rSO2 when SBP reached the nadir during HD were compared between the groups of patients. Results: The cerebral rSO2 before HD in patients with and without symptomatic IDH was 49.7 ± 11.2% and 51.3 ± 9.1% (p = 0.491). %Changes in cerebral rSO2 did not significantly differ between the two groups from 60 min before the SBP nadir during HD. Hepatic rSO2 before HD in patients with and without symptomatic IDH were 58.5 ± 15.4% and 57.8 ± 15.9% (p = 0.869). The %changes in hepatic rSO2 were significantly lower in patients with symptomatic IDH than in those without throughout the observational period (p < 0.001). We calculated the area under the receiver operating characteristic curve (AUC) and estimated cut-off values for changes in hepatic rSO2 as a symptomatic IDH predictor. The predictive ability at 5 and 40 min before symptomatic IDH onset was excellent, with AUCs and cut-off values of 0.847 and 0.841, and -10.9% and -5.0%, respectively. Conclusions: Hepatic oxygenation significantly decreased more in patients with symptomatic IDH before its onset, than in those without symptomatic IDH, whereas changes in cerebral oxygenation did not differ. Evaluating changes in hepatic oxygenation during HD might help to predict symptomatic IDH.